2006
DOI: 10.1016/j.rmed.2005.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Higher BMI is associated with worse asthma control and quality of life but not asthma severity

Abstract: Asthma and obesity tend to co-occur, but relatively few studies have linked obesity, measured using body mass index (BMI), to clinically relevant measures of asthma morbidity. This study assessed BMI in a Canadian sample of asthma Results identify higher BMI and obesity as potential behavioral factors related to worse asthma control and quality of life, but not asthma severity, and suggest important avenues for asthma management and control initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
151
6
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(193 citation statements)
references
References 39 publications
20
151
6
16
Order By: Relevance
“…(32) Our study showed that BMI had a significant effect on QoL of asthmatic children. This was in conform with results of the studies conducted in Canada (33,34) and the United States (35) . The study conducted at Ain Shams university did not show a significant effect for BMI on QoL.…”
Section: Discussionsupporting
confidence: 91%
“…(32) Our study showed that BMI had a significant effect on QoL of asthmatic children. This was in conform with results of the studies conducted in Canada (33,34) and the United States (35) . The study conducted at Ain Shams university did not show a significant effect for BMI on QoL.…”
Section: Discussionsupporting
confidence: 91%
“…14,15 Data on the effect of asthma in children with excessive body weight in the 62 (45) 7 (27) 73 (45) 9 (41) *n, Absolute number for the weight or disease group. %, Percent of total weight or disease group; however, because of missing values, data can be lower or higher than calculated.…”
Section: Discussionmentioning
confidence: 99%
“…52 Lavoiea ve ark.nın çalışmasında, obezitenin astım prevalansını ve insidansını artırarak, astım kontrolünü azalttığı gös-terilmiştir. 53 Hallstrand ve ark.nın çalışmasında, astım ve beden kitle indeksi arasında güçlü bir ilişki olduğu saptanmıştır. Yapılan analizler, obezite genetik bileşenin %8'inin astım ile ortak olduğunu göstermiştir.…”
Section: Astim Ve Obezi̇teunclassified